Main Roof Breakage and Vibration Induced Coal Burst Occurring in Longwall Roadways - Shuangwen Ma; Chen Cao; Qianjia Hui (Shock and Vibration)
Rock burst is one major threat to mining safety and economy. Rock burst occurring in the longwall mining roadway accounts for 85% of the total amount of burst events. This paper investigates the causality mechanism of rock burst in longwall roadways by establishing a finite elastic beam model in the working face based on the elastic foundation theory. The breakage process of the main roof and related dynamic effects are analysed. The result shows that the movement of the main roof shows free vibration under certain damping resistance. It is also found that the roof dominant vibration frequency increases with the increase in the thickness and elastic modulus of the roof. During roof vibration, the vertical stress applied on the coal mass is unloaded. The destressing of the roof-coal interface causes the coal mass in the roadway rib to slip into the roadway under the horizontal ground stress, resulting in rock burst. The possibility of rock burst increases with increase in the strength and thickness of the roof and horizontal ground stress within the coal mass. This mechanism explains the occurrence of rock burst in the mining roadway; it provides the fundamental theory for the prevention and controlling technologies of longwall roadway rock burst.